2022
DOI: 10.3847/1538-4357/ac7648
|View full text |Cite
|
Sign up to set email alerts
|

Inferences on Relations between Distant Supermassive Black Holes and Their Hosts Complemented by the Galaxy Fundamental Plane

Abstract: The realization of fundamental relations between supermassive black holes and their host galaxies would have profound implications in astrophysics. To add further context to studies of their coevolution, an investigation is carried out to gain insight as to whether quasars and their hosts at earlier epochs follow the local relation between black hole mass (M BH) and stellar velocity dispersion (σ *). We use 584 Sloan Digital Sky Survey quasars at 0.2 < z < 0.8 with bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Over the past two decades, various investigations have built an inventory of BH and host measurements to study the redshift evolution of BH-host relations up to z ∼ 3, including the BH mass-stellar velocity dispersion (M BH -σ * ) relation (Treu et al 2004;Woo et al 2006Woo et al , 2010Shen et al 2015b;Sexton et al 2019), the BH mass-bulge/host luminosity (M BH − L *,bulge/host ) relation (Laor 1998;Peng et al 2006aPeng et al , 2006bDecarli et al 2010), and the BH mass-bulge/host stellar mass (M BH -M *,bulge/host ) relation (Jahnke et al 2009;Bennert et al 2011;Dong & Wu 2016;Suh et al 2020;Ding et al 2021), as well as expanding the local baselines to include AGNs of different host properties and lower BH masses (e.g., Greene et al 2008;Jiang et al 2011aJiang et al , 2011bReines & Volonteri 2015;Bentz & Manne-Nicholas 2018;Greene et al 2020;Bennert et al 2021;Zhao et al 2021). Some groups found deviations from local scaling relations as a function of z (Peng et al 2006a(Peng et al , 2006bMerloni et al 2010;Woo et al 2010;Sexton et al 2019), while others found similar BH-host relations to those in the local universe (e.g., Jahnke et al 2009;Suh et al 2020;Li et al 2021a;Ding et al 2022;Silverman et al 2022), which is also supported by the tight correlation between the sampleaveraged BH accretion rate and star formation rate in bulgedominated galaxies at z = 0.5-3 (e.g., Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, various investigations have built an inventory of BH and host measurements to study the redshift evolution of BH-host relations up to z ∼ 3, including the BH mass-stellar velocity dispersion (M BH -σ * ) relation (Treu et al 2004;Woo et al 2006Woo et al , 2010Shen et al 2015b;Sexton et al 2019), the BH mass-bulge/host luminosity (M BH − L *,bulge/host ) relation (Laor 1998;Peng et al 2006aPeng et al , 2006bDecarli et al 2010), and the BH mass-bulge/host stellar mass (M BH -M *,bulge/host ) relation (Jahnke et al 2009;Bennert et al 2011;Dong & Wu 2016;Suh et al 2020;Ding et al 2021), as well as expanding the local baselines to include AGNs of different host properties and lower BH masses (e.g., Greene et al 2008;Jiang et al 2011aJiang et al , 2011bReines & Volonteri 2015;Bentz & Manne-Nicholas 2018;Greene et al 2020;Bennert et al 2021;Zhao et al 2021). Some groups found deviations from local scaling relations as a function of z (Peng et al 2006a(Peng et al , 2006bMerloni et al 2010;Woo et al 2010;Sexton et al 2019), while others found similar BH-host relations to those in the local universe (e.g., Jahnke et al 2009;Suh et al 2020;Li et al 2021a;Ding et al 2022;Silverman et al 2022), which is also supported by the tight correlation between the sampleaveraged BH accretion rate and star formation rate in bulgedominated galaxies at z = 0.5-3 (e.g., Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%